EFFECT OF DIFFERENT HOST PLANTS ON THE LIFE CYCLE OF PAPILIO POLYTES CRAMER (LEPIDOPTERA: PAPILIONIDAE) (COMMON MORMON BUTTERFLY) - Suwarno; M R Che Salmah; A Abu Hassan; A Norani (Tropical Life Sciences Research, 2007)
Investigation on the life cycle of Papilio polytes Cramer (Lepidoptera: Papilionidae) (common mormon butterfly) reared on four host plant species, Citrus aurantifolia Swingle, C. hystrix L., C. reticulata Blanco and Murraya koenigii Sprengle (curry leaf) showed that the butterfly spent the longest larval period on M. koenigii which was significantly different from the time spent on all citrus species. The duration of the pupal stage, however, was the shortest on this host plant. Older instars have longer stadia than the younger instars and the trend of increasing stadium was almost similar in all host plants. No significant differences were detected in the duration of immature stages (larva and pupa), the length and width of pupa and the adult characteristics (length of body, antenna and wingspan) among all citrus species (P = 0.05). However, they were significantly different from individuals reared on M. koenigii. This study revealed that C. reticulata and C. hystrix were the most suitable among the four host plants for this butterfly. The shortest larval duration and life cycle were recorded in the C. reticulata and the biggest pupae and adults occurred on C. hystrix. Murraya koenigii was the least preferred host. Kajian terhadap kitar hidup Papilio polytes Cramer (Lepidoptera: Papilionidae) (rama-rama) ke atas empat jenis tanaman perumah, Citrus aurantifolia Swingle, C. hystrix L., C. reticulata Blanco and Murraya koenigii Sprengel (daun kari) menunjukkan bahawa peringkat larva yang paling lama berlaku pada perumah Murraya koenigii. Jangka masa ini berbeza secara signifikan daripada tiga jenis tanaman limau lain yang diuji. Sungguhpun begitu, jangka masa peringkat pupa pada M. koenigii adalah yang paling pendek. Instar yang lebih tua mempunyai stadium yang lebih lama berbanding instar yang lebih muda dan kecenderungan ini hampir serupa untuk semua jenis perumah. Tiada perbezaan yang signifikan dikesan pada jangka masa pradewasa (larva dan pupa), saiz (panjang dan lebar) pupa dan ciri-ciri dewasa (panjang badan, panjang antena dan lebar sayap) P. polytes terhadap semua jenis tanaman limau (P = 0.05). Walau bagaimanapun, terdapat perbezaan pada larva yang dipelihara dengan M. koenigii. Kajian ini menunjukkan bahawa C. reticulata dan C. hystrix ialah perumah yang lebih sesuai antara empat tanaman yang diuji. Jangka masa larva yang paling singkat direkodkan pada C. reticulata dan saiz pupa dan dewasa yang paling besar direkodkan pada C. hystrix. Murraya koenigii merupakan perumah yang kurang digemari oleh P. polytes.